Investigation of hepatitis E virus seroprevalence and risk factors in hemodialysis patients - Öztürk, Hakkı; Özsoy, Metin; Tuna, Ayşegül; Varlıbaş, Artuner; Cesur, Salih; Aksoy, Altan; Çifci, Aydın; Demir, Mehmet Emin (Frontiers in Public Health, 2025)
BackgroundHemodialysis patients are at increased risk for hepatitis E virus (HEV) infection due to their immunocompromised status and frequent exposure to invasive medical procedures. HEV can lead to chronic infections and severe complications, particularly in high-risk populations. This study aimed to determine HEV-IgG seroprevalence among hemodialysis patients in Ankara, Turkey, and evaluate associated risk factors.MethodsA total of 160 hemodialysis patients from three private dialysis centers in Ankara were included in this prospective, cross-sectional study. Anti-HEV-IgG antibodies were detected using the ELISA method. Demographic characteristics and potential risk factors, including dialysis duration, comorbidities, blood transfusion history, drinking water source, dietary habits, and involvement in animal husbandry, were assessed via structured surveys. Statistical analyses were conducted using SPSS Version 22.0, with Pearson’s chi-square and Fisher’s exact tests applied to categorical variables. Logistic regression analysis was performed to identify independent risk factors for HEV seropositivity.ResultsHEV-IgG seropositivity was detected in 42 patients (26.25%). Seroprevalence increased significantly with age, rising from 6.7% in patients under 55 years to 47.4% in those over 65 years (p < 0.001). Extended dialysis duration (>5 years) was also significantly associated with HEV seropositivity (p = 0.02). However, no significant associations were found between HEV seropositivity and gender, blood transfusion history, source of drinking water, consumption of raw meat, or involvement in animal husbandry (p > 0.05).ConclusionThe HEV-IgG seroprevalence among hemodialysis patients in Ankara was higher than previously reported rates in Turkey. Age and prolonged dialysis duration emerged as significant risk factors, underscoring the importance of screening and preventive strategies in this vulnerable population. Further multi-regional studies are needed to better understand HEV transmission dynamics and improve management strategies in hemodialysis patients.